Report of the Working Group on Khadi and Village Industries for Eighth Plan 1990-95 - Planning Commission (Planning Commission, 1989)
The Order issued by Planning Commission vide their reference No. VSI/14(2)/88 dated 8th August, 1988 read as follows: Sub.: Constitution of the Working Group for Khadi and Village Industries. In the context for the formulation of the Eighth Five Year Plan (1990-95), it has been decided to set up a Working Group for the Khadi & Village Industries.
Planning Commission, Government of India